Change in hippocampal theta activity with transfer from simple discrimination tasks to a simultaneous feature-negative task - Sakimoto, Yuya; Sakata, Shogo (Frontiers in Behavioral Neuroscience, 2014)
It has been shown that solving a simple discrimination task (A+, B-) and a simultaneous feature-negative task (FN) (A+, AB-) uses the hippocampal-independent strategy. Recently, we showed that the number of sessions required for a rat to completely learn a task differed between the FN and simple discrimination tasks, and there was a difference in hippocampal theta activity between these tasks. These results suggest that solving the FN task relies on a different strategy than the simple discrimination task. In this study, we provide supportive evidence that solving the FN and simple discrimination tasks involve different strategies by examining changes in performance and hippocampal theta activity in the FN task after transfer from the simple discrimination task (A+, B- → A+, AB-). The results of this study showed that performance on the FN task was impaired and there was a difference in hippocampal theta activity between the simple discrimination task and FN task. Thus, we conclude that solving the FN task uses a different strategy than the simple discrimination task.